Conceiving Inferential Prototypes of MIMO Channel Models via Buckingham’s Similitude Principle for 30+ GHz through THz Spectrum - Neelakanta, Perambur; De Groff, Dolores (Discoveries in Agriculture and Food Sciences, 2021)
Facilitating newer bands of ‘unused’ segments (windows) of RF spectrum falling in the mm-wave range (above 30+ GHz) and seeking usable stretches across unallocated THz spectrum, could viably be considered for Multiple Input Multiple Output (MIMO) communications. This could accommodate the growing needs of multigigabit 3G/4G applications in outdoor-based backhauls in picocellular networks and in indoor-specific multimedia networking. However, in contrast with cellular and Wi-Fi, wireless systems supporting sub-mm wavelength transreceive communications in the outdoor electromagnetic (EM) ambient could face “drastically different propagation geometry”; also, in indoor contexts, envisaging pertinent spatial-multiplexing with directional, MIMO links could pose grossly diverse propagation geometry across a number of multipaths; as such, channel-models based on stochastic features of diverse MIMO-specific links in the desired test spectrum of mm-wave/THz band are sparsely known and almost non-existent. To alleviate this niche, a method is proposed here to infer sub-mm band MIMO channel-models (termed as “prototypes”) by judiciously sharing “similarity” of details available already pertinent to traditional “models” of lower-side EM spectrum, (namely, VLF through micro-/mm-wave). Relevant method proposed here relies on the “principle of similitude” due to Edgar Buckingham. Exemplar set of “model-to-(inferential)-prototype” transformations are derived and prescribed for an exhaustive set of fading channel models as well as, towards estimating path-loss of various channel statistics in the high-end test spectrum.